A STUDY OF DOWRY SYSTEM IN JAMMU AND KASHMIR - PRIKSHA RAINA (International Journal of Economic, Business, Accounting, Agriculture Management and Sharia Administration (IJEBAS), 2024)
The practice of paying dowry is widespread throughout Jammu & Kashmir, especially in the district of Jammu. Daughters became a curse and a liability for their parents, which resulted in severe repercussions. In India, the practice is banned or limited by the Dowry Prohibition Act, 1961, which was extended to the Union territory of Jammu and Kashmir after the abrogation of Article 370. Even though the law protects it, the tradition has grown. Dowry appears to be increasing as a result of changes in lifestyle and social trends. To find out what men and women think about dowry, how it affects people, why it's important, and how it affects women's rights and, in the long run, their freedom. A qualitative study was carried out. Men and women, including social activists, economists, and married couples, were asked about wedding costs, demands, social pressure, men's support, and how they felt about dowry, especially in terms of women's rights in unstructured interviews. The study found that a large dowry, especially in the form of furniture, electronics, kitchenware, a car, a fully furnished house, and cash, was strongly linked to women's growth and rights. The widespread belief among individuals is that the practice of paying a dowry is no longer considered to be a custom or tradition. It's just a trend, but many are following it as a sign of respect for women and mothers in particular.